The effect of a self-management program through a mobile application on lipid profile among persons with coronary artery disease: A randomized controlled trial study in Thailand - Rapin Polsook; Yupin Aungsuroch (Belitung Nursing Journal, 2026)
Background: Cholesterol, triglycerides, and low-density lipoprotein levels are key indicators of patients’ self-care in coronary artery disease; although medications can improve lipid profiles, the results often remain above targets. Implementing mobile self-management programs is crucial for reducing the incidence of coronary artery disease, preventing cardiac events, and enhancing well-being. Objective: This study aimed to evaluate the impact of a self-management program on cholesterol, triglycerides, and low-density lipoprotein levels in people with coronary artery disease. Methods: A randomized controlled trial design was employed at a tertiary hospital in Thailand between June 2022 and June 2023. Forty-eight people were randomly assigned to one of two groups: control or experimental. The experimental group used applications and the telephone for four weeks to self-manage cholesterol, triglyceride, and low-density lipoprotein levels, while the control group received conventional care. Data were gathered about cholesterol, triglyceride, and low-density lipoprotein levels. Descriptive statistics, independent t-tests, and dependent t-tests were employed to analyze between-group and within-group differences. Effect sizes (Cohen’s d) with 95% confidence intervals were calculated. Results: Results showed that the experimental group had a statistically significant reduction in cholesterol (t = 2.121, df = 46, p = 0.039), triglyceride (t = 2.060, df= 46, p = 0.046), and low-density lipoprotein levels (t = 2.115, df = 46, p = 0.040) compared to the control group. This study demonstrates that a mobile application self-management program can lower lipid levels. Conclusions: The findings indicate that a mobile application–based self-management program can significantly reduce cholesterol, triglyceride, and low-density lipoprotein levels in people with coronary artery disease in the short term. These findings highlight the crucial role of nurses applying these strategies to enhance patient care. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250129001)